Genetic justice: DNA data banks, criminal investigations, and civil liberties - Krimsky, Sheldon (Columbia Univ. Press, 2011)
Forensic DNA analysis -- The network of U.S. DNA data banks -- Community DNA dragnets -- Familial DNA searches -- Forensic DNA phenotyping -- Surreptitious biological sampling -- Exonerations : when the DNA doesn't match -- The allure behind universal data banks -- The UK : paving the way to forensic DNA -- Japan's forensic DNA data bank : a call for reform -- Australia : a quest for uniformity in DNA data banking -- Germany : from eugenics to forensics -- Italy : a data bank in search of a law -- Privacy and genetic surveillance -- Racial disparities in DNA data banking -- Fallibility in DNA identification -- Efficacy : a case of diminishing returns -- Toward a vision of justice : recommendations for responsible uses of DNA in law enforcement -- Appendix: Six-country comparison of forensic DNA data banks